Safety of CDK4/6 inhibitors and concomitant radiation therapy in patients affected by metastatic breast cancer. (December 2022) - Visani, Luca; Livi, Lorenzo; Ratosa, Ivica; Orazem, Miha; Ribnikar, Domen; Saieva, Calogero; Becherini, Carlotta; Salvestrini, Viola; Scoccimarro, Erika; Valzano, Marianna; Cerbai, Cecilia; Desideri, Isacco; et al.
Highlights: CDK4/6 inhibitors represent the standard-of-care for metastatic HR+/HER2 breast cancer. Available data on CDK4/6 inhibitors and concomitant RT are conflicting. We showed that concurrent RT did not increase treatments severe toxicity. A consensus guideline to help physician's routine practice is strongly needed. Abstract: Purpose: Cyclin-dependent kinase 4/6 inhibitors (CDK4/6i) currently represent the standard of care for the initial treatment of patients with metastatic hormone receptor-positive/human epidermal growth factor receptor 2-negative (HR+/HER2-) breast cancer. The aim of our study is to evaluate the safety of the use of concomitant radiation therapy (RT) in a consecutive series of HR+/HER2- patients treated in two academic institutions with CDK4/6i in the metastatic setting. Methods and materials: From September 2017 to February 2020, we retrospectively collected and analysed data on a sequential series of patients treated with CDK4/6i, receiving RT or not, at two European institutions. Primary outcome of the study was the association between RT and any adverse events (AEs) ≥ G3. Secondary outcomes were the association between RT and any AEs (any grade), CDK4/6i dose reduction rate, and CDK4/6i treatment discontinuation rate. Results: We analysed a total of 132 consecutive women; RT was prescribed in 57 (43.2%) patients (70 irradiated lesions). The median age of the series was 52.1 years (range 32.3–78.2). Concomitant RT administration was not significantly related to higher AEs ≥ G3 (p = 0.19) and any grade AEs (p = 1.0); there was no association with RT and CDK4/6i dose reduction (p = 0.49) and discontinuation rates (p = 0.14). At a median follow-up of 18.8 months, the progression-free survival (PFS) rate was 35% and the overall survival (OS) rate was 38.7% in the whole group. The use of concomitant RT did not affect both PFS (p = 0.71) and OS rates (p = 0.55). Conclusions: Our data are encouraging regarding the safety of this combination, showing that concurrent RT did not increase severe toxicity and did not have an impact on systemic treatment conduction.